The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1002/mrm.27593
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous multi‐slice cardiac cine with Fourier‐encoded self‐calibration at 7 Tesla

Abstract: Purpose To accelerate cardiac cine at 7 tesla using simultaneous multi‐slice (SMS) acquisition with self‐calibration to resolve misalignment between calibration and imaging data due to breathing motion. Methods A spoiled‐gradient echo cine sequence was modified with radiofrequency phase‐cycled SMS excitations. A Fourier encoding strategy was applied along the cardiac phase dimension to allow for slice untangling and split‐slice GRAPPA calibration. Split‐slice GRAPPA was coupled with regular GRAPPA (SMS‐GRAPPA)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 36 publications
(50 reference statements)
0
18
0
Order By: Relevance
“…For instance, the GRE length could be shortened using undersampling, k‐space‐weighted image contrast, or compressed sensing, which could then be used to reduce aliasing artifacts. Parallel imaging would also enable simultaneous MS acquisition, thus extending applications of the MS‐MP2RAGE sequence to whole‐body T 1 mapping.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the GRE length could be shortened using undersampling, k‐space‐weighted image contrast, or compressed sensing, which could then be used to reduce aliasing artifacts. Parallel imaging would also enable simultaneous MS acquisition, thus extending applications of the MS‐MP2RAGE sequence to whole‐body T 1 mapping.…”
Section: Discussionmentioning
confidence: 99%
“…A prospectively electrocardiographic-triggered cardiac PC 2D cine MR sequence with three-directional velocity encoding 30 was extended to include k-t acceleration 13 and autocalibrated MB CAIPIRINHA. 28,29 This combination is not straightforward, because for each technique certain conditions with respect to the sampling patterns and the RF phases have to be fulfilled. Before presenting the rationale for the combination of the two techniques, a brief introduction to autocalibrated MB CAIPIRINHA and k-t acceleration is provided.…”
Section: Sequence Descriptionmentioning
confidence: 99%
“…The benefits of MB have been demonstrated in cardiac MRI, [19][20][21][22][23][24][25][26][27] and the technique was recently extended to TPM with one-directional velocity encoding. 28 Two recent studies have also demonstrated the benefit of autocalibrated MB, 28,29 a variant of MB-CAIPIRINHA encoding that does not require external reference scans for the reconstruction, thus limiting the number of required breath-holds to only one.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that g-factor noise enhancement with appropriate CAIPIRINHA shifting of slices will not be the limiting factor on multiband acceleration in cardiac bSSFP. Although MB2 acceleration has negligible impact on image quality, residual unfolding artefacts begin to appear with higher MB factors (3)(4), predominantly effecting the basal slices. These are more evident Figure 5, the mean and [max] value increased from 1.13 [2.20] to 1.46 [3.63]).…”
Section: In Vivo Evaluation Of Frequency Responsementioning
confidence: 99%